Pelaksanaan Program SUN-Movement dalam Penanggulangan Kasus Stunting: Literature Review - Della, Della Anggraini Putri; Misnaniarti; Anita Rahmiwati (Jurnal Kesehatan Komunitas, 2023)
The high incidence of stunting in Indonesia according to SSGI data in 2021 is 24.4% (WHO Target 20%). One of the prevention and control efforts from the government is the Scaling Up Nutrition (SUN) movement, which is the first 1000 days of life movement based on Presidential Regulation No. 72 of 2021 by carrying out specific interventions. This article aims to analyze the implementation of the SUN-Movement program in overcoming stunting cases. This research uses a literature review method that reviews 9 articles. The articles reviewed were based on the results of screening by reading all and only focusing on SUN-Movement, Stunting Program, Stunting Program, and Stunting. The results of the review of 9 articles in 7 districts in west Indonesia, that of the 9 specific interventions in the SUN-Movement policy, 6 interventions were identified that had been carried out such as in Aceh Besar and Subang exclusive breastfeeding was implemented. Consuming blood supplement tablets for adolescent girls and supplementary nutrition for pregnant women has been implemented in Palembang, Subang, and Bebes. Supplementary food for toddlers in Demak has been implemented. Complementary feeding for infants over 6 months has been implemented in Semarang and Pasaman. However, interventions for toddlers such as nutrition care services, growth and development monitoring, and complete basic immunization have not been implemented. It was revealed that about 3 specific intervention programs in 7 districts in Indonesia had not been implemented.